Tick species from cattle in the Adama Region of Ethiopia and pathogens detected - Tafese Beyene Tufa; Silke Wölfel; Dana Zubriková; Bronislava Víchová; Martin Andersson; Ramona Rieß; Liliana Rutaihwa; André Fuchs; Hans Martin Orth; Dieter Häussinger; Torsten Feldt; Sven Poppert; et al. (Experimental and Applied Acarology, 2021)
Ticks will diminish productivity among farm animals and transmit zoonotic diseases. We conducted a study to identify tick species infesting slaughter bulls from Adama City and to screen them for tick-borne pathogens. In 2016, 291 ticks were collected from 37 bulls in Adama, which were ready for slaughter. Ticks were identified morphologically. Total genomic DNA was extracted from ticks and used to test for Rickettsia spp. with real-time PCR. Species identification was done by phylogenetic analysis using sequencing that targeted the 23S-5S intergenic spacer region and ompA genes. Four tick species from two genera, Amblyomma and Rhipicephalus , were identified. Amblyomma cohaerens was the dominant species (n = 241, 82.8%), followed by Amblyomma variegatum (n = 22, 7.5%), Rhipicephalus pulchellus (n = 19, 6.5%), and Rhipicephalus decoloratus (n = 9, 3.0%). Among all ticks, 32 (11%) were positive for Rickettsia spp. and 15 (5.2%) of these were identified as R. africae comprising at least two genetic clades, occurring in A. variegatum (n = 10) and A. cohaerens (n = 5). The remainder of Rickettsia -positive samples could not be amplified due to low DNA yield. Furthermore, another 15 (5.2%) samples carried other pathogenic bacteria: Ehrlichia ruminantium (n = 9; 3.1%) in A. cohaerens , Ehrlichia sp. (n = 3; 1%) in Rh. pulchellus and A. cohaerens , Anaplasma sp. (n = 1; 0.5%) in A. cohaerens , and Neoehrlichia mikurensis (n = 2; 0.7%) in A. cohaerens. All ticks were negative for Bartonella spp., Babesia spp., Theileria spp., and Hepatozoon spp. We reported for the first time E. ruminatium , N. mikurensis , Ehrlichia sp., and Anaplasma sp. in A. cohaerens. Medically and veterinarily important pathogens were mostly detected from A. variegatum and A. cohaerens. These data are relevant for a One-health approach for monitoring and prevention of tick-borne disease transmission.